AIDS and pregnancy: meanings of risk and challenges for care - Silva, Neide Emy Kurokawa e; Alvarenga, Augusta Thereza de; Ayres, José Ricardo de C M (Revista de Saúde Pública, 2006)
OBJECTIVE: To understand how the risk of vertical HIV transmission is perceived and interpreted by people living with HIV/AIDS, when making decisions regarding reproductive health. METHODS: This was a qualitative study carried out at three municipal health clinics specializing in STD/AIDS, in the city of São Paulo. Semi-structured thematic interviews were conducted with eight patients (male and female), from July to December 2001. The interviewees were key informants and either they or their partners were seropositive. All of them were aged 18 or over and had been living with their partners for at least one year. RESULTS: Among the motivations for having children, those related to the partner's expectations were highlighted, especially as a form of "recompense" for their actions. The risk of vertical transmission was used by health professionals both for discouraging pregnancy and for giving guidance on transmission prophylaxis. However, reproductive issues were not voiced at the health clinics, either by the patients or by the healthcare providers. CONCLUSIONS: Attention should be directed not only towards controlling the infection, but also most importantly towards the wellbeing of people living with HIV/AIDS. There is a need to clarify the different points of view of users and professionals in order to achieve the most effective and appropriate solution for each specific caregiving situation.